The Effect Of Aloe Vera On Healing Process Of Incision Wound - Mahandaru, Danu; Dachlan, Ishandono (Jurnal Plastik Rekonstruksi, 2012)
Considering the advantages of wound treatment in moist-state, many practitioners always keep the wound in the moist condition. One of the alternatives is by using aloe vera. It has moisturizing effect, anti inflammatory and can stimulate growth factor and fibroblast. In this study, the authors aim to compare the effect of the wound dressing with the dry gauze, moist gauze and aloe vera toward the tensile strength. Thirty Rattus Novergicus were divided into two experimental groups and 1 control group. We performed full thickness skin incision on the back of the rats, and then we sutured and nursed them by using moist gauze and Aloe Vera while the dry gauze group treated as the control. On the 10th day, we decapitated the rats and we took the trace of incisional skin for the tensile strength test. At last, the samples were measured by Zwick universal tensile strength testing machine. This research show that the group treated by dry gauze had tensile strength (35 ± 7 N/cm2) , with moist gauze (41 ± 7 N/cm2), and with Aloe Vera (68 ±17 N/cm2). There was a significant difference between the three groups regarding the tensile strength (p<0.001). Treatment of wound by using Aloe Vera is proven to be more effective than the dry gauze and moist gauze to increase the tensile strength.